Oregano - Padulosi, S. (1997)
Four multicrop germplasm collecting missions took place in Albania during 1993-95 which collected 5 accessions of oregano, subsequently deposited at the Germplasm Institute in Bari, Italy. This paper briefly considers the geographical distribution and taxonomy of Origanum in Albania and includes information on its cultivation and uses. (Abstract © CAB ABSTRACTS, CAB International)